Peran Pemerintah dalam Pengelolaan Sampah di Pasar Sentral Rappang Kecamatan Panca Rijang Kabupaten Sidenreng Rappang - Nurmi Surahma Dilla; Sapri, Sapri; Hardianti Laduppa; Abdul Jabbar (Yayasan Literasi Sains Indonesia, 2025)
This study aims to examine the government's waste management practices at Pasar Sentral Rappang, Panca Rijang District, Sidenreng Rappang Regency, and to formulate strategic steps that can enhance the effectiveness of waste management in the area. The waste management issues in this market are complex, marked by waste accumulation, inadequate storage facilities, and a shortage of personnel and equipment. This research employs a qualitative methodology, collecting data from six key informants—community members, market managers, cleaning staff, government organizations, and market visitors—through in-depth interviews, observation, and documentation. Data analysis was conducted using NVivo software through processes of coding, thematic analysis, and data visualization. The results show that the government's role in waste management has not been fully optimized. This is evident from weaknesses in planning, organizing, mobilizing, and controlling. The lack of supporting infrastructure, limited number of transport vehicles, low public participation, and poor inter-agency coordination are major challenges to establishing an effective waste management system. The application of public management principles based on George R. Terry's approach is identified as a potential solution to improve management effectiveness, including the development of integrated planning, public education, and stronger collaboration among the government, market administrators, and local communities. This study emphasizes the need to strengthen institutional capacity, improve infrastructure, and implement continuous education programs as steps toward participatory and sustainable waste management.